Penile prosthetic surgery for the management of Peyronie’s disease - Raheem, Omer A.; Hsieh, Tung-Chin (Translational Andrology and Urology, 2017)
With the increased prevalence of Peyronie’s disease (PD) among men, there is also an up-rise of associated erectile dysfunction (ED) which can be devastating psychologically and sexually to most men. A wide range of therapies including medical and surgical procedures are available to satisfactorily address this condition. However when ED coexists, the gold standard treatment is penile prosthetic prosthesis (PP) with or without additional straightening procedures. We herein systematically review the contemporary literature addressing the role of the PP in the management of PD with concomitant ED with particular emphasis on patient’s satisfaction, outcomes and safety.